A new fitness function for tuning parameters of Peripheral Integral Derivative Controllers - Odili, Julius Beneoluchi; Noraziah, Ahmad; Babalola, Asegunloluwa Eunice (Elsevier, 2021)
In recent years, the need for greater effectiveness and efficiency in industrial processes and procedures has made control system engineering a favored area of scientific investigation, especially the proper tuning of the parameters of Peripheral Integral Derivative (PID) Controllers. This paper critically examines some issues with the present fitness functions being used by different researchers involved in metaheuristic tuning of PID Controllers. It concludes with the introduction of a fitness function called the Inverse Integrated Squared Absolute Error whose experimental outcome using the African Buffalo Optimization algorithm was able to obtain zero (0) steady state error, zero (0) overshoot, 1.77 s rise time and 2.87 s steady time which is quite competitive. The paper opines that further appropriate investigations of the metaheuristic tuning of PID Controllers using this latest fitness function are highly recommended since it is very simple to both implement and use.